Inovasi Pemanfaatan Teknologi Sebagai Media Pembelajaran di Era Revolusi 4.0 - Budiyono, Budiyono (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2020)
This study aims to examine the use of technology technique as a learning media and teacher innovation to overcome the problem. By library research, the researcher conducted the relevant literature study to answer the research and explained it descriptively. The results of the study indicate that optimization on the use of instructional media was done by understanding the characteristics of media and learning needs. Technology controller was the teacher, not the teacher depending on technology. Teacher needs innovation when facing the limitations or facing other technical obstacles. Teacher can maximize everything that can be used to deliver learning information, including the use of the environment. So, something real can be presented applicatively.